Statins in the treatment of chronic heart failure: a systematic review. - Pim van der Harst; Adriaan A Voors; Wiek H van Gilst; Michael Böhm; Dirk J van Veldhuisen (PLoS Medicine)
Background The efficacy of statin therapy in patients with established chronic heart failure (CHF) is a subject of much debate. Methods and findings We conducted three systematic literature searches to assess the evidence supporting the prescription of statins in CHF. First, we investigated the participation of CHF patients in randomized placebo-controlled clinical trials designed to evaluate the efficacy of statins in reducing major cardiovascular events and mortality. Second, we assessed the association between serum cholesterol and outcome in CHF. Finally, we evaluated the ability of statin treatment to modify surrogate endpoint parameters in CHF. Using validated search strategies, we systematically searched PubMed for our three queries. In addition, we searched the reference lists from eligible studies, used the "see related articles" feature for key publications in PubMed, consulted the Cochrane Library, and searched the ISI Web of Knowledge for papers citing key publications. Search 1 resulted in the retrieval of 47 placebo-controlled clinical statin trials involving more than 100,000 patients. CHF patients had, however, been systematically excluded from these trials. Search 2 resulted in the retrieval of eight studies assessing the relationship between cholesterol levels and outcome in CHF patients. Lower serum cholesterol was consistently associated with increased mortality. Search 3 resulted in the retrieval of 18 studies on the efficacy of statin treatment in CHF. On the whole, these studies reported favorable outcomes for almost all surrogate endpoints. Conclusions Since CHF patients have been systematically excluded from randomized, controlled clinical cholesterol-lowering trials, the effect of statin therapy in these patients remains to be established. Currently, two large, randomized, placebo-controlled statin trials are under way to evaluate the efficacy of statin treatment in terms of reducing clinical endpoints in CHF patients in particular.